Phytotoxin of Fusarium avenaceum on broadbean - AL- HAMDANY, M.A. (Indian Phytopathology, 2002)
F. avenaceum [Gibberella avenacea] was isolated from diseased broad bean plants and cultured in Czapeks broth at 25é³¦ for 2 weeks. The culture filtrate was assayed by soaking the roots of 20-day-old seedlings of faba bean (Vicia faba), cucumber, bottle gourd (Lagenaria siceraria), barley, okra (Abelmoschus esculentus), sesame and wheat in the filtrate for 24 h. Wilting symptoms on broadbean, cucumber, okra and sesame seedlings indicated the presence of a phytotoxin in the culture filtrate of G. avenacea.